The Development of a Scaffolding-Based Instructional Model for Learners with Intellectual Disabilities - Munir Yusuf; Nur Fakhrunnisaa (International Journal of Learning Reformation in Elementary Education, 2026)
Students with intellectual disabilities (also known as children with intellectual impairments) are individuals with below-average intelligence. Despite their cognitive limitations, these children still possess great potential to grow and excel in certain areas. This potential greatly depends on appropriate treatment that meets their specific needs. This study aims to design and develop a scaffolding-based learning model for students with intellectual disabilities at Sekolah Luar Biasa Negeri 1 Palopo (The Special Needs School 1 Palopo). This research employs Collaborative Action Research to identify students' Zone of Proximal Development, integrated into a Research and Development (4D) framework. The 4D stages (Define, Design, Develop, Disseminate) were conducted to construct the module and media. The subjects were 6 students with mild-to-moderate intellectual disabilities (Grades 2 to 5). The intervention consisted of two sessions (2x30 minutes) using customized number sticks and puzzles. Data collection techniques included observation, interviews, and tests, while data analysis was conducted using both quantitative and qualitative approaches. The results of the study indicate that the development process of the scaffolding-based learning model for students with intellectual disabilities at Sekolah Luar Biasa Negeri 1 Palopo consists of four stages: define, design, develop, and disseminate. Disseminate, generating learning tools in the form of teaching modules and instructional média, which have been developed and are considered suitable for use and considered to be valid.